Defective DNA repair: a putative nexus linking immunological diseases, neurodegenerative disorders, and cancer - Andarawi, Safaa; Vodickova, Ludmila; Uttarilli, Anusha; Hanak, Petr; Vodicka, Pavel (Mutagenesis, 2025)
DNA damage is a common event in cells, resulting from both internal and external factors. The maintenance of genomic integrity is vital for cellular function and physiological processes. The inadequate repair of DNA damage results in the genomic instability, which has been associated with the development and progression of various human diseases. Accumulation of DNA damage can lead to multiple diseases, such as neurodegenerative disorders, cancers, immune deficiencies, infertility, and ageing. This comprehensive review delves the impact of alterations in DNA damage response genes (DDR) and tries to elucidate how and to what extent the same traits modulate diverse major human diseases, such as cancer, neurodegenerative diseases, and immunological disorders. DDR is apparently the trait connecting important complex disorders in humans. However, the pathogenesis of the above disorders and diseases are different and lead to divergent consequences. It is important to discover the switch(es) that direct further the pathogenic process either to proliferative, or degenerative diseases. Our understanding of the influence of DNA damage on diverse human disorders may enable the development of the strategies to prevent, diagnose, and treat these diseases. In our article, we analysed publicly available GWAS summary statistics from the NHGRI-EBI GWAS Catalog and identified 12 009 single-nucleotide polymorphisms (SNPs) associated with cancer. Among these, 119 SNPs were found in DDR pathways, exhibiting significant P-values. Additionally, we identified 44 SNPs linked to various cancer types and neurodegenerative diseases (NDDs), including four located in DDR-related genes: ATM, CUX2, and WNT3. Furthermore, 402 SNPs were associated with both cancer and immunological disorders, with two found in the DDR gene RAD51B. This highlights the versatility of the DDR pathway in multifactorial diseases. However, the specific mechanisms that regulate DDR to initiate distinct pathogenic processes remain to be elucidated.
Keywords: celogenomová asociační studie; NHEJ; Polymorphism, Single Nucleotide; Humans; neurodegenerativní nemoci; DNA damage; DNA repair; oprava DNA; nemoci imunitního systému; jednonukleotidový polymorfismus; Immune System Diseases; neurodegenerative disorders; cancer; human diseases; lidé; nestabilita genomu; DNA damage response; genomic instability; DNA Repair; Genetic Predisposition to Disease; genetická predispozice k nemoci; Neoplasms; HR; autoimmune diseases; nádory; Genome-Wide Association Study; poškození DNA; DNA Damage; Genomic Instability; Neurodegenerative Diseases; MMR; NER; BER